Luminal Cholera Toxin Alters Motility in Isolated Guinea-Pig Jejunum via a Pathway Independent of 5-HT3 Receptors - Fung, Candice; Ellis, Melina; Bornstein, Joel C. (Frontiers in Neuroscience, 2010)
Cholera toxin (CT) is well established to produce diarrhoea by producing hyperactivity of the enteric neural circuits that regulate water and electrolyte secretion. Its effects on intestinal motor patterns are less well understood. We examined the effects of luminal CT on motor activity of guinea-pig jejunum in vitro. Segments of jejunum were cannulated at either end and mounted horizontally.Their contractile activity was video-imaged and the recordings were used to construct spatiotemporal maps of contractile activity with CT (1.25 μg/ml or 12.5 μg/ml) in the lumen. Both concentrations of CT induced propulsive motor activity in jejunal segments. The effect of 1.25 μg/ml CT was markedly enhanced by coincubation with granisetron (5-HT3 antagonist, 1 μM), which prevents the hypersecretion induced by CT. The increased propulsive activity was not accompanied by increased segmentation and occurred very early after exposure to CT in the presence of granisetron. Luminal CT also reduced the pressure threshold for saline distension evoked propulsive reflexes, an effect resistant to granisetron. In contrast, CT prevented the induction of segmenting contractions by luminal decanoic acid, so its effects on propulsive and segmenting contractile activity are distinctly different. Thus, in addition to producing hypersecretion, CT excites propulsive motor activity with an entirely different time course and pharmacology, but inhibits nutrient induced segmentation. This suggests that CT excites more than one enteric neural circuit and that propulsive and segmenting motor patterns are differentially regulated.